Implementation of Sales Forecasting Method In Production Planning In Cv Tirta Alam Jaya Merauke - Alfons, Marlyn Eleida; Batlajery, Semuel (Universitas Pendidikan Ganesha, 2018)
The problem to be studied is how the sales forecasting method is applied in the company and what variables influence sales forecasting. with the aim, for the company can apply optimal sales forecasting method for the survival of the company and know the variables that affect sales forecasting. In this study the data obtained then tested by the following methods: (1) Linear Trend Analysis Method, General equation form (Sofyan Assauri, 1984, pp. 53-56): Y = a + bt, (2) Method of Exponental Trends (a) Constant, with forecasting function: (b) Linear, with the logarithmic method, Y = a + b log t The function of this method is: forecasting function: Y_t = a + bt and (4) Decomposition Method. Result of research The best forecasting method to predict the sales of bottled drinking water in CV Tirta Alam Jaya Merauke in the next period, is the method of Exponental Trend. This method is chosen because it has the lowest error rate value when compared with other forecasting method, that is for forecasting sales Bottled drinking water obtained MAD value of 932.65, MSE of 20,581,918.63 and MAPE of 34.94%. Sales forecasting results Bottled drinking water using Exponental trend method calculation is 14,104 Carton in January 2016